2017
DOI: 10.15171/jpd.2018.05
|View full text |Cite
|
Sign up to set email alerts
|

Serum magnesium in association with parathyroid hormone levels in routine hemodialysis patients

Abstract: Introduction: The homeostasis of magnesium (Mg) is perturbed in chronic kidney disease. It has been supposed that plasma Mg has a principal role to regulate the secretion of parathyroid hormone (PTH). Plasma Mg is capable of modulating secretion of PTH. Recent investigations showed that low serum Mg levels in patients with kidney disease have been linked to increased mortality. Objectives: The aim of this study was to determine the relationship between serum Mg and PTH levels in hemodialysis patients. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In addition, the results of these studies are also conflicting (8,9). The results of the study by Fooladgar et al showed a positive relationship between iPTH and serum Mg levels among HD patients, however most of other studies in HD patients and also most of studies among ESRD patients undergoing peritoneal dialysis showed a significant inverse relationship between serum Mg and serum intact PTH levels (1,8,9). Therefore, as Fooladgar et al recommended, there still remains a number of big questions about this issue and it is necessary to further evaluate of role of Mg in secondary hyperparathyroidism and vascular calcification.…”
Section: Dear Editormentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the results of these studies are also conflicting (8,9). The results of the study by Fooladgar et al showed a positive relationship between iPTH and serum Mg levels among HD patients, however most of other studies in HD patients and also most of studies among ESRD patients undergoing peritoneal dialysis showed a significant inverse relationship between serum Mg and serum intact PTH levels (1,8,9). Therefore, as Fooladgar et al recommended, there still remains a number of big questions about this issue and it is necessary to further evaluate of role of Mg in secondary hyperparathyroidism and vascular calcification.…”
Section: Dear Editormentioning
confidence: 99%
“…With great interest, we read the recently published article entitled "serum magnesium in association with parathyroid hormone levels in routine hemodialysis patients" by Fooladgar and colleagues in Journal Parathyroid Disease (1). They evaluated, in a cross-sectional study, the serum levels of magnesium (Mg), calcium, phosphorus and intact PTH (iPTH) among 56 end-stage renal disease (ESRD) patients undergoing maintenance hemodialysis (HD) in a HD center (1).…”
Section: Dear Editormentioning
confidence: 99%
See 3 more Smart Citations